Implementasi Nilai-Nilai Moral Etik Melalui Pembelajaran Pedagogi Dengan Pendekatan Artificial Ilntelligence Dalam Membentuk Karakter Peserta Didik - Wahab, Gusnarib A.; Rahmah, Hikmatur (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Moral issues are a matter of thought and common concern because Indonesian society is currently experiencing a moral crisis. This crisis is marked by the rise in criminal acts, such as brawls between students, increasing promiscuity, the surge in violence against children and adolescents, sexual harassment, the rise in motorcycle gangs and muggers, which often lead to acts of violence that disturb society. This phenomenon has tarnished the image of students and educational institutions, as many people hold the view that such conditions originate from the world of education itself. The development of technology has positive and negative impacts, and also presents its challenges, especially in the field of education. In the field of education, technological transformation is increasingly rapid, along with the development of artificial intelligence technology. AI not only provides changes to teaching methods but also creates opportunities to improve the quality and effectiveness of learning. Teachers are increasingly encouraged to develop their competencies to reach a level of professionalism. Teachers utilise various types of human resources to develop pedagogical competencies.